Radiologic Features Of Anencephaly : A Serial Case Report - Nadia Citradibyaguna; Besari Adi Pramono; Farah Hendara Ningrum; Sukma Imawati (Medica Hospitalia : Journal of Clinical Medicine, 2025)
Background : Anencephaly is a lethal central nervous system anomaly characterized by absence of cerebral structures and cranial vault. It is the most common open neural tube defect that occurs in 0.5 – 2 per 1,000 live births. This anomaly can be detected as early as 11 weeks of pregnancy by transvaginal ultrasonography. Micronutrient deficiency, such as anemia and folic acid deficiency, was known to be the potential risk factor for anencephaly. Case Report : We reported 4 cases of anencephaly diagnosed using ultrasonography during pregnancy. All patients were referred to Dr. Kariadi General Hospital from private hospitals in Central Java. 3 out of 4 cases were diagnosed in the first trimester and 1 case was diagnosed in the third trimester. Ultrasonography features showed typical signs of anencephaly including ‘frog eyes sign’, ‘Mickey mouse sign’ and acrania. All of the patients underwent termination of pregnancy with variable route of delivery according to each patients’ condition and gestational age. Discussion : Routine antenatal ultrasonography is recommended for early detection of fetal viability and other congenital anomalies including anencephaly. Ultrasonography is able to detect typical findings of anencephaly and therefore is able to accurately establish the diagnosis. Advanced imaging technique such as MRI is unnecessary unless diagnosis using ultrasonography is indeterminate. Establishing the diagnosis of anencephaly is very important due to determining its definitive treatment, in which termination of pregnancy. Conclusion : In this serial case series, we present various radiologic features of anencephaly using ultrasonography so that clinicians will be able to diagnose this anomaly in earlier age of pregnancy. Hence, definitive treatment can be done and complications during pregnancy can be prevented.